ANALYSIS OF HEAVY METALS CONTENT AS A KEY INDICATOR TO PREDICT SHALLOW-SLOPE FAILURE - Othman, Rashidi; Hasni, Shah Irani; Baharuddin, Zainul Mukrim (IWA PUBLISHING, 2017)
Degradation or decline of soil quality that cause shallow slope failure may occur due to physical or chemical pro¬cesses. It can be triggered off by natural phenomena, or induced by humans through misuse of land resources, excessive development and urbanization leads to deforestation and erosion of the covered soil masses that causing serious threat to slopes. The extent of damages of the slopes could be minimized if a long-term early warning system to predict the landslide prone areas would have been in place. The aim of the study is to characterize chemical properties of stable and unstable slope along selected highways in Malaysia which can be manipulated as indicator to forecast shallow slope failure. Those elements in soil chemical properties contributed to each other as binding agents that affects the existing soil structure. It could make the soil structure strong or weak .In conclusion, indicators that can be used to predict shallow slope failure are low content of Ferum ( Fe), Plumbum (Pb),Aluminum (Al), Chromium ( Cr), Zinc (Zn), low content of organic carbon and CEC.